Radiation dose intensity and local tumour control of non-small cell lung cancer: A radiobiological modelling perspective. (June 2019) - Alaswad, M; Kleefeld, C; Foley, M
Abstract: Several clinical situations call for the use of radiobiological principles as powerful clinical tools. The aim of this project is to examine the effect of radiotherapy dose intensity on local tumour control for non-small cell lung cancer (NSCLC) using the biological effective dose (BED) concept. A two-year tumour control probability (TCP) model was developed based on the linear-quadratic cell concept combined with Poisson statistics. The two-year local control outcome was analysed for the radiotherapy dose using the BEDs. The BED calculations and the TCP model were fitted to a series of NSCLC patients drawn from the literature. The investigation is based on the two-year local tumour control rate for stage I-II NSCLC for a dose fractionation size that varied from 1.5-20 Gy per fraction delivered via three radiotherapy treatments: 3D-conformal radiation therapy (3D-CRT), continuous hyperfractionated accelerated radiotherapy (CHART) and stereotactic ablative body radiotherapy (SABR). The BED values of 2, 280 patients were computed and analysed as a function of local tumour control. To quantitatively assess the correlation between the BED and local tumour control, a residuals analysis and linear regression were performed. Higher radiotherapy doses were associated with improved local tumour control and survival rates for NSCLC, as suggested by the coefficient of the correlation R 2 statistical test: 0.83 for the 3D-CRT and 0.91 for the SABR treatment.